Saving behavior of Tabung Haji customer in Melaka: A case study in Melaka Tengah / Norazilah Mustafa - Mustafa, Norazilah (Faculty of Business and Management, 2006)
The last two decades have witnessed the emergence of Islamic banking as a viable banking system. Since 1971, Islamic banks have continued to grow in size and in numbers. The main mission of these financial institutions has been the achievement of social and economic development through the delivery of financial services in line with the principles and teachings of Islam. It same for Tabung Haji to provide a variety quality facilities and services for the welfare, health and proper control as well overall protection for Muslims in Holy Land when performing HajL The emergence of commercial bank gives big implication for Tabung Haji run their business. With growing competitiveness in the banking industry and similarity of services offered by banks, it has become increasingly important that Tabung haji identify the factor that determine the basic upon which customer choose financial services. This research focuses in studying the saving behavior of Tabung Haji customer in Melaka: a case study in Melaka Tengah. Therefore this research is designed to identify the correlation between saving and income, saving determinants of Tabung Haji depositors which involve demographic profile of the customer and bank selection criteria of Tabung Haji customers. The study sample comprised 60 customers. A profile analysis of respondent, mean analysis of bank selection criteria, correlation between saving and income and simple regression analysis were conducted. Findings revealed that the important factor selection criteria both financial institution and Tabung Haji were: confidence of financial institution, friendliness of bank personnel and bank reputation. In addition, there are correlation between saving and income, moreover the study indicate age, income and job classification were determinants of saving.